THE INFLUENCE OF DISTRIBUTION CHANNEL COST ON SALES VOLUME IN SARANA TANI MANADO - Parengkuan, Greny Estherfien Olyvia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
The direction of fertilizer distribution is no longer based on the allocation of the needs of customers but already based on the magnitude of the benefits. This condition is very influenced by the selling price and the cost of fertilizer distribution. The use of distribution channels and pricing are very important, because it can affect the sales volume, the level of capital gains, risks, and the benefits. The general objective of each industry is certain to make a profit, and it will be achieved if the sales activities can be carried out successfully as planned. Cost element in the distribution of activity became an important thing because without the cost, the distribution will not running. This research will explain more about the influence of distribution channel cost on sales volume in Sarana Tani Manado that sell and provide the fertilizers, usually marketed in the field of agriculture in the region. This research method used associative group analysis. From the financial report that was taken from Sarana Tani Manado, there are three independent variables in distribution channel cost (transportation cost, warehouse cost and packing cost) that influence the sales volume. The findings showed that transportation cost and packing cost are the significant variables of distribution channel cost that influence sales volume, while warehouse cost is not the significant variable of distribution channel cost that influence sales volume in Sarana Tani, Manado. Keywords: distribution channel, sales volume, transportation cost, warehouse cost, packing cost.